Mortality of Sardinian lead and zinc miners: 1960-88. - Cocco, P L (1994)
The mortality of 4740 male workers of two lead and zinc mines was followed up from 1960 to 1988. Exposure to respirable dust was comparable in the two mines, but the median concentration of silica in respirable dust was 10-fold higher in mine B (12.8%) than in mine A (1.2%), but the mean annual exposure to radon daughters in underground workplaces differed in the opposite direction (mine A: 0.13 working levels (WL), mine B: 0.011 WL). Total observed deaths (1205) were similar to expected figures (1156.3) over a total of 119 390.5 person-years at risk. Underground workers of mine B had significant increases in risk of pulmonary tuberculosis (SMR 706, 95% confidence interval (95% CI) 473-1014) and non-malignant respiratory diseases (SMR 518; 95% CI 440-1606), whereas the only significant excess at mine A was for non-malignant respiratory diseases (SMR 246; 95% CI 191-312). Total cancer and lung cancer mortality did not exceed the expectation in the two mines combined. A 15% excess mortality for lung cancer, increased up to an SMR 204 (95% CI 89-470) for subjects employed > or = 26 years, was, however, found among underground workers in mine A who on the average experienced an exposure to radon daughters 10-fold higher than those of mine B. By contrast, despite their higher exposure to silica, mine B underground workers experienced a lower than expected lung cancer mortality. A ninefold increase in risk of peritoneal and retroperitoneal cancer combined was also found among underground workers of mine A (SMR 917; 95% CI 250-2347; based on four deaths). A causal association with workplace exposures is unlikely, however, as the SMR showed an inverse trend by duration of employment. These findings are consistent with low level exposure to radon daughters as a risk factor for lung cancer among metal miners. Exposure to silica at the levels estimated for the mine B underground environment did not increase the risk of lung cancer.